Kebijakan Perhutanan Sosial yang Responsif Gender : Studi Kasus Peraturan Perundang-Undangan Bidang Perhutanan Sosial Dan Pemberian Izin Perhutanan Sosial - Enik Ekowati; Muamar Syamsudin (Jurnal Perempuan, 2022)
This article focuses on two issues; whether the Directorate General of Social Forestry and Environmental Partnership has integrated gender issues into laws and regulations and policy implementation, and whether these issues have been applied to the granting of Social Forestry permits. This study uses empirical legal research methods to assess the application of gender issues in the Social Forestry Regulations and Permit Policy. The results of this study indicate an increase in the number of Social Forestry provisions that regulate gender issues. That is, in the Minister of Environment and Forestry Regulation No. 83 of 2016 there are two articles that regulate gender issues, whereas in the Minister of Environment and Forestry Regulation No. 9 of 2021 there are seven articles. The integration of gender responsive articles and the implementation of gender responsive practices has led to significant changes such as the management by women of two Social Forestry Business groups, Katimpun Village and Damaran Village. This process represents the first step of positive change in the implementation of gender mainstreaming policies in environmental issues in the Ministry of Environment and Forestry.